2019
DOI: 10.1186/s12879-019-4417-1
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularis inoculation induces NK cell functional decrease through high expression of NKG2A in C57BL/6 mice

Abstract: Background Alveolar echinococcosis (AE) is caused by the larval stage of Echinococcus multilocularis (E. multilocularis), and considered as public health issue. Parasite-host immune interaction is pivotal during infection. As a subset of innate lymphoid cells, NK cells are known to play an important role during virus, bacteria, intra/extracellular parasitic infections and tumor progression. However, the possible role of NK cells in E. multilocularis infection in both human and murine is little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Mice were sacri ced at experimental timepoints (180 days after model was established) using euthanasia, which was approved by Institutional Animal Care and Use Committee. Speci cally, mice were intraperitoneally (left lower quadrant) injected with 5% chloral hydrate 0.15-0.20 ml/mouse through medical syringe needle, and peripheral blood was collected by retro-orbital bleeding after successfully anesthetized; then, whole liver and spleen samples were obtained surgically; at last, mice were euthanized using cervical dislocation [13].…”
Section: Specimen Collectionmentioning
confidence: 99%
“…Mice were sacri ced at experimental timepoints (180 days after model was established) using euthanasia, which was approved by Institutional Animal Care and Use Committee. Speci cally, mice were intraperitoneally (left lower quadrant) injected with 5% chloral hydrate 0.15-0.20 ml/mouse through medical syringe needle, and peripheral blood was collected by retro-orbital bleeding after successfully anesthetized; then, whole liver and spleen samples were obtained surgically; at last, mice were euthanized using cervical dislocation [13].…”
Section: Specimen Collectionmentioning
confidence: 99%
“…11,12 In AE, E. multilocularis infection inhibits the activity and proliferation of NK cells, implying that NK cells in AE patients with alveolar hydatid cannot perform normal immune surveillance functions, which leads to the formation of immune tolerance. 13,14 A recent study has demonstrated that E. multilocularis can downregulate the immune response of NK cells by inducing the overexpression of NKG2A on the surface of NK cells. In addition, some studies have also found that the sustained expression of MICA/B molecules and TGF-β may lead to the inhibition of NKG2D in NK cells, 15 thereby inhibiting NKG2D-dependent cytotoxicity, and causing immune escape of E. multilocularis in host's NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Portal vein injection is also used in murine models for the development of pathologies such as liver metastasis ( Goddard et al., 2016 ; Orci et al., 2018 ) and parasitic diseases ( Nakaya et al., 1997 ; Jarillo-Luna et al., 2002 ; Chen et al., 2017 ; Zhang et al., 2017a , 2017b ; Cortes et al., 2019 ; Abulizi et al., 2019 ). These procedures require laparotomy and therefore must be performed under anesthesia and analgesia to prevent or minimize the discomfort, pain, and/or distress of mice ( Flecknell, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported the use of different anesthesia protocols (inhalational or injectable) to perform laparotomy and subsequent intraportal injection of an agent in mice ( Arnheiter et al., 1976 ; Nakaya et al., 1997 ; Jarillo-Luna et al., 2002 ; Chen et al., 2017 ; Kawaguchi et al., 2017 ; Zhang et al., 2017a , 2017b ; Sherman et al., 2014 ; Goddard et al., 2016 ; Orci et al., 2018 ; Abulizi et al., 2019 ; Cortes et al., 2019 ). However, only a few studies have described the use of analgesic for pain management and it was applied at the end of the surgical procedure ( Jarillo-Luna et al., 2002 ; Sherman et al., 2014 ; Goddard et al., 2016 ; Orci et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation